КРЕДИТ ТАЪЛИМДА ЭКОЛОГИЯ ВА ТАБИАТНИ МУҲОФАЗА ҚИЛИШ ФАНИДАН АУДИТОРИЯ МАШҒУЛОТЛАРИНИ ОЛИБ БОРИШ - Ҳушвақтова, Ҳ.С. (SCIENCE and SOCIETY, 2022)
The article examines the organization of educational processes in the credit-module system, conducting audience classes on the subject of "Ecology and nature protection" in higher educational institutions, and the types and stages of educational activities.
Keywords: education; credit-module system; self-study; credit scores; assessment